The Effectiveness of the e-Wetland Book Integrated Reading-Questioning-Answering for Geography Learning in Wetland Environments - Nevy Farista Aristin; Eva Alviawati; Sovia Husni Rahmia (JAMBURA GEO EDUCATION JOURNAL, 2026)
Students' knowledge of wetland concepts is quite diverse due to the very complex presentation of wetland material. This is one of the primary challenges in the geography learning process in the era of Education 4.0, particularly in the Regional Development Geography course. Learning components that incorporate the use of learning resources and the selection of appropriate learning strategies, integrated with technology, play a crucial role in improving and maintaining students' knowledge in the long term. To address this challenge, it is essential to develop a digital book on wetlands that integrates Reading-Questioning-Answering RQA). The purpose of this study was to measure the effectiveness of the E-Wetland Book Integrated RQA in improving wetland area development knowledge among students at Lambung Mangkurat University. The subjects were 30 students taking the Regional Development Geography course in the Geography Education Study Program at Lambung Mangkurat University, as all students had relatively similar reading and cognitive literacy skills. This study employed a pre-experimental design with a one-group pretest-posttest-only design. The analysis used a paired sample t-test. The e-wetland book, which integrates RQA, enables students to learn about wetland development related to tourism, settlements, transportation, and agriculture in South Kalimantan. The implementation of the e-wetland book, integrated with RQA during classroom learning activities, can enhance students' knowledge, critical and creative thinking skills, speaking abilities, and overall learning outcomes. The implications of developing an e-wetland book integrated with RQA can provide an alternative approach to digital learning resources and effective learning strategies, thus improving student learning outcomes and the quality of learning in the digital era.